Internet of Things Workshop at SMK Darussalam Tarogong Kaler Garut - Erwid M. Jadied; Muhammad Al Makky (JAPATUM: Jurnal Pemanfaatan Teknologi untuk Masyarakat, 2022)
SMK Darussalam Tarogong Kaler (SMK Darussalam) has a vision of "Forming creative, innovative, noble, responsible, and able to participate in global society". To help realize the vision and mission of SMK Darussalam, the graduates must be competent in accordance with their respective fields of expertise and skills. Currently, the direction of industrial or community needs for technology is in the field of IoT (Internet of Things). The implementation of IoT in Indonesia currently has enough opportunities. The potential of IoT is believed to be very large and is a business in the future. The above conditions are an opportunity for Darussalam Vocational School to have competence in the field of networking and IoT. Opportunities for teachers and students of SMK Darussalam to design systems that are supported by IoT devices.